Fusion gene addiction: can tumours be forced to give up the habit?1. Issue 3 (29th May 2017) - Selfe, Joanna L; Shipley, Janet
Abstract : Linked Article: Pandey et al.J Pathol 2017; 241: 626‐637 . Abstract: Fusion of genes in tumours can have oncogenic roles in reprogramming cells through overexpression of oncogenes or the production of novel fusion proteins. A fundamental question in cancer biology is what genetic events are critical for initiation and whether these are also required for cancer progression. In recent work published in The Journal of Pathology, dependency on a fusion protein was addressed using a model of alveolar rhabdomyosarcomas – a sarcoma subtype with frequent fusion of PAX3 and FOXO1 genes that is associated with poor outcome. PAX3–FOXO1 encodes a potent transcription factor that together with MYCN alters the transcriptional landscape of cells. Building on previous work, an inducible model in human myoblast cells was used to show that PAX3–FOXO1 and MYCN can initiate rhabdomyosarcoma development but, contrary to current thinking, tumour recurrences occasionally arose independent of the fusion protein. Further work needs to identify the molecular nature of this independence and assess any relevance in human tumours. Such functional approaches are required together with computational modeling of molecular data to unravel spatial and temporal dependencies on specific genetic events. This may support molecular prognostic markers and therapeutic targets. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.